1987
DOI: 10.1099/00221287-133-11-3219
|View full text |Cite
|
Sign up to set email alerts
|

Proline-induced Germ-tube Formation in Candida albicans: Role of Proline Uptake and Nitrogen Metabolism

Abstract: Proline-induced germ-tu be formation and cell-cell aggregation in four strains of Candida albicans were completely inhibited when the pH of the medium was 5.0 or lower, whereas morphogenesis induced by N-acetylglucosamine (GlcNAc) was unaffected even at pH 4.5. The pH sensitivity of proline-induced germ-tube formation was not caused by a modulation of proline uptake, which was unchanged over the pH range 4.5-6.5. The proline uptake system was specific, constitutive and subject to ammonium repression, and only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 27 publications
(20 reference statements)
4
31
0
Order By: Relevance
“…Amino acids other than those mentioned in the 2). These results are consistent with those of L-proline uptake in intact cells (Table 2) (Jayakumar et al, 1978(Jayakumar et al, , 1979(Jayakumar et al, , 1981Dabrowa & Howard, 1981;Holmes & Shepherd, 1987).…”
Section: Solubilization and Purification Of The Proline Permeasesupporting
confidence: 90%
See 3 more Smart Citations
“…Amino acids other than those mentioned in the 2). These results are consistent with those of L-proline uptake in intact cells (Table 2) (Jayakumar et al, 1978(Jayakumar et al, , 1979(Jayakumar et al, , 1981Dabrowa & Howard, 1981;Holmes & Shepherd, 1987).…”
Section: Solubilization and Purification Of The Proline Permeasesupporting
confidence: 90%
“…The purified permease demonstrated stereospecific binding and other characteristics which were consistent with earlier studies on uptake of L-proline in C. albicans cells (Dabrowa & Howard, 1981;Holmes & Shepherd, 1987;Jayakumar et al, 1978Jayakumar et al, , 1979Jayakumar et al, , 1981. However, clear proof that it is purified proline permease lies with the fact that it can also mediate L-proline translocation in a reconstituted system.…”
Section: Reconstitution Of Proline Permease In Proteoliposomessupporting
confidence: 89%
See 2 more Smart Citations
“…Recent studies (Holmes & Shepherd, 1987, 1988 have indicated that changes in nitrogen metabolism are involved in the control of morphogenesis in Candida albicans. The ammonium assimilation enzymes have a central role in nitrogen metabolism, and the aim of this study was to compare the nature and activities of these enzymes in C. albicans and other Candida spp.…”
Section: A R Holmes a N D Othersmentioning
confidence: 99%